Mitigating the impact of adolescence isolation on the development of social anxiety: A potential role for oxytocin - Johnston, Morgan P.; Wanat, Matthew J. (Frontiers in Behavioral Neuroscience, 2022)
Exposure to isolation can lead to the development of social anxiety disorder (SAD), which affects 13% of Americans. There are sex differences in the prevalence of anxiety disorders, as women experience higher rates of SAD relative to men. Importantly, isolation experienced during adolescence increases the likelihood of developing SAD in adulthood. Unfortunately, the current treatments for SAD are only effective in 50-65% of patients. As such, it is critical to identify therapeutic targets for the treatment and prevention of SAD, particularly in women. Here, we discuss the links between childhood isolation and adulthood SAD. Next, we examine the preclinical models used to study the impact of isolation on social anxiety-like behaviors in rodents. Increasing evidence from both clinical and pre-clinical studies suggests oxytocin signaling is a potential target to modify social anxiety-like behaviors. We present the evidence that sex hormones influence oxytocin system. Finally, we highlight future directions for both clinical and pre-clinical studies to further evaluate the efficacy of oxytocin as a treatment for isolation-induced SAD.